Exchange Structure in The United States Presidential Election Debate 2024: Donald Trump and Kamala Harris - Maryam Ulfa; Muhammad Yusuf; Fikry Prastya Syahputra (LingPoet: Journal of Linguistics and Literary Research, 2025)
This study analyzes the 2024 U.S. presidential election debate between Donald Trump and Kamala Harris using the Interpersonal Function framework, specifically Exchange Structure (Move) from Systemic Functional Linguistics (SFL). The analysis identifies five Move patterns: "K1", "K2^K1", "K1^K2F", "K1^K2F^K1F", and "A1", along with one dynamic move pattern: Challenge and Response to Challenge (CH-RCH). The findings reveal that Donald Trump adopts a more authoritative and responsive stance in the debate, frequently assuming the role of Primary Knower (K1) to assert his knowledge and authority. He is more engaged in responding to challenges (RCH) rather than initiating them, indicating a focus on defending his credibility. In contrast, Kamala Harris actively challenges (CH) Trump's statements, often taking the Secondary Knower (K2) role by questioning or scrutinizing his claims before asserting her own position. However, she also assumes the Primary Knower (K1) role at times to establish her authority. Trump's debate strategy is centered on defending and reinforcing his credibility, while Harris employs a more confrontational approach, challenging Trump's assertions to cast doubt on his statements. This study contributes to the understanding of power dynamics and interactional strategies in political debates through an SFL-based discourse analysis.